THE COMMODIFICATION OF PUBLIC-PRIVATE PARTNERSHIPS: EVIDENCE OF COMMODIFICATION AND RESTRICTION OF FREE ACCESS TO PUBLIC GOODS (Editora Impacto Científico, 2025)
Public-Private Partnerships (PPPs) have emerged as an important instrument for the effective provision of public services. In addition to the need for legal frameworks and regulatory and oversight tools, it is essential to ensure that the delivery of public services is effectively adequate to meet users' needs, thereby satisfying, among other legal requirements, the principles of universality and affordability of tariffs. In this context, the implementation of public services—such as in airports, ports, highways, subways, sanitation and housing works, education (non-pedagogical support), parks, and bioparks—must observe such principles, among others. Hence arises the current dilemma and relevant debate surrounding the characterization of adequate services in light of the right of economic exploitation inherent to PPPs, taking into account their particular legal logic. This analysis seeks to establish the boundaries for proper PPP operations and to identify evidence of misuse or deviation from legal frameworks, thus preventing the phenomenon of "VIP treatment" or exclusion within PPPs. Employing the deductive method, as well as statistical data from recent PPPs, the research aims to address situations where commodification and restricted access to public goods are present.DOI: https://doi.org/10.56238/edimpacto2025.090-058